(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article explores the current issues of intercultural communication through the lens of literary translation in the context of the interaction between the Russian and Uzbek languages. The author analyzes the concepts of "translation adequacy" and "translation equivalence," the challenges of conveying national realities and idioms, and the role of the translator as a mediator of cultures. The article provides recommendations for improving the quality of translation and fostering intercultural communication through the use of modern translation methods and technologies. Special attention is given to preserving the ethnocultural uniqueness of the original while achieving equivalence.